COVID-19 in Colombia: repercussions on the economy - Hernández Rodríguez, Danilo (SUMMA, 2022)
This research shows the effects of COVID-19 on various economic sectors globally and on the Colombian market. The negative effects on the economy due to the mandatory restrictions imposed by the governments of each country are reflected in the high rate of unemployment, low demand for informal employment and closures of businesses and/or enterprises. Therefore, the largest drop in GDP on the European continent occurred in France and the United Kingdom with 11.4% and 11.5%, respectively. In Latin America the greatest economic impact received was the reduction in investment, obtaining a value of approximately 85%, and in Colombia the GDP fell considerably by -15.7% due to many factors caused by the measures imposed to prevent the spread of the virus. In addition, economic activities such as industrial production had a fall of -35.6% in March, the manufacturing sector decreased by -25.4% and the construction sector by approximately -31% in the month of june.